Perbandingan Pendidikan Madrasah di Thailand dan Filipina - Mauliya Nandra Arif Fani; Kholid Mawardi (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2024)
Madrasas are educational institutions that combine the national curriculum with the Islamic curriculum. Madrasa education is an alternative to advancing education in the midst of the times. In various countries, especially in Muslim minority countries in the Southeast Asian region, for example Thailand and the Philippines, madrasas are educational institutions that enable people to get an education, if they cannot afford to go to public educational institutions. Madrasas were once considered inferior in terms of their education system, but this did not solely apply to all madrasas, or more precisely, the education system in madrasas has now undergone modernization so as to allow for a better quality of education with combined scientific dualism, namely religion and science. general. Therefore, this paper aims to discuss, describe, and analyze the madrasah education system in the Southeast Asian region, in this case in Thailand and the Philippines. The research uses qualitative research methods with a library research approach. Madrasah education in basic Thailand starts from the ibtidaiyah level, then continues with mutawassitha, and continues at the final level, namely tsanawiyah. Meanwhile in the Philippines, there are madrasah madrasas, regular madrasah madrasas, and integrated madrasas. Regular madrasah diniyah have levels of education similar to the madrasah education system in Thailand. Keywords: Islamic Education, Madrasah Education, Thai Islamic Education, Philippine Islamic Education, Southeast Asian Islamic Education